Co-diseño y co-creación de experiencias de realidad aumentada: una revisión sistemática de la literatura - Bacca-Acosta, Jorge; Beltran-Sanchez, Karen (Revista Científica, 2024)
Augmented reality is gaining more and more interest in fields such as education, medicine, tourism, marketing, and manufacturing. However, the creation of this type of applications has been dominated by software development methodologies, and only recently have co-design and co-creation approaches been integrated to favor a more effective development to meet specific needs. This paper reports the results of a systematic literature review of 40 scientific articles on the co-design and co-creation of augmented reality experiences, with the aim of providing a landscape of the current state of research in this field. The results show that most augmented reality experiences have been co-designed or co-created for the fields of education and engineering. Moreover, most of the current research has followed an exploratory and cross-sectional approach with small and medium research samples, using classical methods for data collection. Overall, there is an increasing interest in the use of co-design and co-creation methodologies for developing augmented reality experiences. This paper also presents some trends and future lines of work.